Retracted: Internet of Things Health Detection System in Steel Structure Construction Management - Qinglin Liu; Yongjiang Zhu; Xiongzhou Yuan; Jian Zhang; Rui Wu; Qianwen Dou; Song Liu (IEEE Access)
In recent years, the development of computer network technology, especially the hot Internet of things, has brought great convenience and comfort to people’s life. Steel structure is also more and more widely used in the field of construction in China. The purpose of this study is to explore the application of Internet of things health monitoring system in steel structure construction management. In this study, through the use of example analysis, comprehensive data analysis and other methods, combined with steel structure health monitoring system and construction process management analysis. The results show that the relative deviation of the data within 1–33 is mostly less than 10%, but the relative deviation of 34–40 suddenly increases to 60%, and the actual data suddenly decreases, resulting in the deviation of about 50%. It is concluded that the time series model established in this study can objectively reflect the change trend and law of strain data, has certain prediction accuracy, and has certain value significance for monitoring data analysis and construction management of steel building structures.